Inventory Management is a Crucial Issue in Supply Chain Management / Al Ain Hospital - Ayman Mustafa Al Armouti; Amal Salem Al Kabi (AIBPM Publisher, 2018)
The paper is discussed about survey that includes several questions that is related to the research topic to know what employees are employees’ point of view and how many of the employees are facing the same problem regarding this issue, this can be seen by the graphical results that I would prepare on excel through the questioner results. The paper discusses each aspect about the inventory management that why there is this issue and what should be done to deal with this issue to make the inventory system that includes supply chain management more effective and advance. There are some issues in the warehouse itself that can be improved to solve this issue but this topic includes many topics to be shared and go to their details to know the depth of the issue and the reason behind this problem. The topics will cover the problems, the identification of the problems, the characteristics, the reasons, objectives, the solution, analysis of the problem and many more topics that includes some paragraphs of the discussion on the regarding issues. Each and every topic includes details and discussion of the same issue to know what is the reason behind it what are the roots beneath the issue that is growing this problem into a big tree with the branches as personally me is facing this issue that if some product is not available in the warehouse is a problem, so these are some highlights that will be discussed below. The research can make me able to make some prospective to give ahead some improved solution to the organization to get efficient and accuracy in the systems od supply chain management that can help hospital to operate various function to some extent. On the second hand the research is very helpful to me in a way it can help me in knowing various departments and function more deeply and carefully which can help me in improving my skills and knowledge. The end of this paper included the opinions and solutions that will be discussed and details with own experience and work or tasks done in entire paper.